2018
DOI: 10.1186/s12943-018-0766-4
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the regulatory role of microRNA in tumor angiogenesis and clinical implications

Abstract: Angiogenesis is essential for tumor growth and metastasis. Understanding the regulation of tumor angiogenesis has become increasingly important. MicroRNAs (miRNAs) are small noncoding RNAs that function in diverse biological processes via post-transcriptional regulation. Extensive studies have revealed two important regulatory roles of miRNAs in tumor angiogenesis: miRNAs in tumor cells affect the activity of endothelial cells via non-cell-autonomous mechanisms, and miRNAs in endothelial cells regulate the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 134 publications
(135 reference statements)
0
122
0
Order By: Relevance
“…miRNA controls different aspects of BC angiogenesis and tumor progression by regulating apoptosis, proliferation, motility, energy metabolism, etc. More than forty miRNAs [48] were identified to be associated with tumor angiogenesis. Among the angiomiRs, miRNA-155, miRNA-153, miRNA-206, miRNA-467, miRNA-21, miRNA-34a and miRNA-126 respond to glucose level, miRNA-105, miRNA-206, miRNA-236 and miRNA-190 regulate metastasis, and miRNA-205, miRNA-206, miRNA-296, miRNA-34a and miRNA-98 control proliferation and thus control endothelial physiology and tumor angiogenesis ( Table 1).…”
Section: Mirna In Ec Vegf Signalingmentioning
confidence: 99%
“…miRNA controls different aspects of BC angiogenesis and tumor progression by regulating apoptosis, proliferation, motility, energy metabolism, etc. More than forty miRNAs [48] were identified to be associated with tumor angiogenesis. Among the angiomiRs, miRNA-155, miRNA-153, miRNA-206, miRNA-467, miRNA-21, miRNA-34a and miRNA-126 respond to glucose level, miRNA-105, miRNA-206, miRNA-236 and miRNA-190 regulate metastasis, and miRNA-205, miRNA-206, miRNA-296, miRNA-34a and miRNA-98 control proliferation and thus control endothelial physiology and tumor angiogenesis ( Table 1).…”
Section: Mirna In Ec Vegf Signalingmentioning
confidence: 99%
“…It has been estimated that cancer cells can only reach a maximum volume of 1-2 mm 3 in the absence of a vascular system [110]. In order for tumors to proliferate and metastasize, angiogenesis must first take place, and miRNAs have been described to regulate this process [111][112][113]. Lin et al observed that miR-30d promotes angiogenic proliferation and migration, and enhances the ability of PCa cells to recruit endothelial cells via myosin phosphatase targeting subunit 1 (MYPT1)/c-JUN/VEGF-A pathway (Fig.…”
Section: Mirnas In Tumor Microenvironmentmentioning
confidence: 99%
“…Histone acetylase overexpression, which catalyzes the removal of acetyl groups on the tail of histones, is another mechanism of transcriptional repression that leads to chromatin remodeling and genome instability in lung cancer [62]. miRNAs play important roles in different cellular processes including cell development and proliferation, differentiation, growth control, and apoptosis [9,11]. It was shown that miRNAs can regulate the expression of at least 30% of genes that control various biological functions [63,64].…”
Section: Epigenetic Factors In the Development Of Cancermentioning
confidence: 99%
“…Therefore, miRNA are involved in multiple biological processes, including gene regulation, cell development and proliferation, maintenance of cell differentiation, growth control, and apoptosis. Now it is well estimated that one-third of human genes are regulated by miRNAs and miRNAs play a key role in regulatory mechanisms of many cell function [10,11,63].…”
Section: Epigenetic Factors In the Development Of Cancermentioning
confidence: 99%
See 1 more Smart Citation